Development And Assessment Of Acalypha Indica Soap: Exploring In Vitro Antimicrobial Properties - P. Jegadeeswari, P. Jegadeeswari; R. Prasanth, R. Prasanth; Jayaprakash, B.N.; G. Asha, G. Asha; S. Anbazhagan, S. Anbazhagan; S.A. Vadivel, S.A. Vadivel (Journal of Neonatal Surgery, 2025)
Specifically, the development and evaluation of a herbal soap that contains Acalypha indica extract is the focus of this research program., known for its antimicrobial properties. The soap was developed using traditional Cold process method and evaluated for its physicochemical properties, antimicrobial efficacy, and skin benefits. The plant extract was analyzed for saponins, alkaloids, flavonoids, tannins, and steroids. The products were tested for antibacterial activity against Staphylococcus aureus, Bacillus spp., Escherichia coli, and Klebsiella spp. using the agar well diffusion method. The results suggest that Acalypha indica-based soap exhibits significant antimicrobial activity, making it a potentially effective alternative to commercial soaps for maintaining skin hygiene..